Palavras navegáveis: um estudo da poética de Lúcio Lins - Fernandes, Aglaé Maria Araújo (2003)
Starting with a survey of the most recurrent technical and stylistic procedures in Lúcio Lins, poetic work, this research point at its main characteristics, namely: antithetical constructions, transtextual relations and na isotopy of navigation. Based on this isotopy, and in the light of a Gaston Bachelard´s ideas about the poetic text, and, at the same time, enchances the metapoetic meaning which concentrates on the investigation of the element that constitute the material imagination of Líns poetics: the water.